Body composition status and the risk of migraine: A meta-analysis. (9th May 2017) - Gelaye, Bizu; Sacco, Simona; Brown, Wendy J.; Nitchie, Haley L.; Ornello, Raffaele; Peterlin, B. Lee
Abstract : Objective: To evaluate the association between migraine and body composition status as estimated based on body mass index and WHO physical status categories. Methods: Systematic electronic database searches were conducted for relevant studies. Two independent reviewers performed data extraction and quality appraisal. Odds ratios (OR) and confidence intervals (CI) were pooled using a random effects model. Significant values, weighted effect sizes, and tests of homogeneity of variance were calculated. Results: A total of 12 studies, encompassing data from 288, 981 unique participants, were included. The age- and sex-adjusted pooled risk of migraine in those with obesity was increased by 27% compared with those of normal weight (odds ratio [OR] 1.27; 95% confidence interval [CI] 1.16–1.37, p < 0.001) and remained increased after multivariate adjustments. Although the age- and sex-adjusted pooled migraine risk was increased in overweight individuals (OR 1.08; 95% CI 1.04, 1.12, p < 0.001), significance was lost after multivariate adjustments. The age- and sex-adjusted pooled risk of migraine in underweight individuals was marginally increased by 13% compared with those of normal weight (OR 1.13; 95% CI 1.02, 1.24, p < 0.001) and remained increased after multivariate adjustments. Conclusions: The current body of evidence shows that the risk of migraine is increased in obese and underweight individuals. Studies are needed to confirm whether interventions that modify obesity status decrease the risk of migraine.